Validated Ion Pair HPLC Method For Simultaneous Estimation Of Ceftriaxone Sodium And Tazobactum Sodium In Dosage Form - M.GANDHIMATHI; M.SARAVANAKUMAR; T.K.RAVI (International Journal of Pharma and Bio Sciences, 2010)
A simple, sensitive and rapid ionpair high performance liquid chromatographic methodwas developed for the estimation ceftriaxone sodium (CS) and tazobactum sodium (TS) in pharmaceutical dosage forms. LichrocartR100-RP18e5µm-C18 column was used with a mobile phase containing mixture of 0.012M tetra butyl ammonium hydroxide in 0.01M potassium dihydrogen phosphate : acetonitrile in the ratio of 70:30 v/v. The flow rate was 0.8ml/min and effluents were monitored at 220nm and eluted at 4.5 and 6.7 min for tazobactum sodium (TS) and ceftriaxone sodium (CS) respectively. Calibration curve was plotted with a range from 2 to 12 µg/ml (CS) and 0.26 to 1.56 (TS) µg/ml. The assay was validated for the parameters like accuracy, precision, robustness and syste m suitability parameters. The proposed method can be useful in the routine analysis for the determination of ceftriaxone sodium and tazobactum sodium in pharmaceutical dosage forms.